Humanized Mouse Model of Mast Cell-Mediated Passive Cutaneous Anaphylaxis and Passive Systemic Anaphylaxis - Bryce, Paul J. (J Allergy Clin Immunol, 2016)
BACKGROUND: Mast cells are a critical component of allergic responses in humans, and animal models that allow the in vivo investigation of their contribution to allergy and evaluation of new human-specific therapeutics are urgently needed. OBJECTIVE: We have developed a new humanized mouse model that supports human mast cell engraftment and human IgE-dependent allergic responses. METHODS: This model is based on the NOD-scid IL2rg(null) SCF/GM-CSF/IL3 (NSG-SGM3) strain of mice engrafted with human thymus, liver and hematopoietic stem cells (termed BLT). RESULTS: Large numbers of human mast cells develop in NSG-SGM3 BLT mice and populate the immune system, peritoneal cavity, and peripheral tissues. The human mast cells in NSG-SGM3 BLT mice are phenotypically similar to primary human mast cells and express CD117, tryptase, and FcεRI. These mast cells undergo degranulation in an IgE-dependent and independent manner, and can be readily cultured in vitro for additional studies. Intradermal priming of engrafted NSG-SGM3 mice with a chimeric IgE containing human constant regions resulted in development of a robust passive cutaneous anaphylaxis (PCA) response. Moreover, we describe the first report of a human mast cell antigen-dependent passive systemic anaphylaxis (PSA) response in primed mice. CONCLUSIONS: NSG-SGM3 BLT mice provide a readily available source of human mast cells for investigation of mast cell biology and a pre-clinical model of PCA and PSA that can be used to investigate the pathogenesis of human allergic responses and to test new therapeutics prior to their advancement to the clinic.